Incidencia de las infecciones respiratorias y su relación con la neumonía en niños menores de 5 años que acuden a la unidad anidada del Hospital “Dr. Juan Montalván Cornejo” del cantón Urdaneta durante el segundo semestre del 2013 - Galarza Contreras, Gabriela Julieta (2013)
In Ecuador Acute Respiratory Infections (ARI) are the leading cause of health care demand, and are responsible for 20 to 40% of outpatient visits for children and 12-35% of hospital admissions. In Juan Cornejo Montalván Hospital, based in the parish of Canton Urdaneta Ricaurte and unit class care hospital facility called nested top-level pathologies such as IRA, in the second half of 2013 serves as data provincial epidemiology this unit attended 735 cases of uncomplicated pneumonia and IRAS. This research seeks to determine respiratory infections and its relationship with pneumonia in children under 5 years attending the nested unit of Hospital aforementioned For these reasons it is necessary to study the Trouble Of Respiratory Infections And Your Relationship With Pneumonia In Children And Girls Under 5 Year Flocking A Nested Unit Hospital "Dr. Juan Montalvan Cornejo "From Canton Urdaneta During The Second Half Of 2013 This research led us to determine that the vast majority of people live in houses ventilated, with good space and keep good hygiene measures, the environment, where they are located together factor to climate and customs of the people, they are constituents predispose respiratory tract infections. In this research, it can be noted that despite that there was a high incidence of acute respiratory infections, pneumonias were 5% in relation to the total cases of infection Acute Respiratory when cases expected under epidemiological surveillance should be less 10% in this sector of the country, thus Aborting our hypothesis claiming that is the generation of respiratory diseases related to increased pneumonia in children below 5 years attending the nested unit of the Hospital "Dr. Juan Cornejo Montalván "Ricaurte in the second half of 2013.?.